Stir bar sorptive extraction of aroma compounds in soy sauce: Revealing the chemical diversity. (June 2021) - Diez-Simon, Carmen; Eichelsheim, Charlotte; Jacobs, Doris M.; Mumm, Roland; Hall, Robert D.
Graphical abstract: Highlights: Stir bar sorptive extraction-GCMS is a robust method to analyse soy sauce volatiles. Untargeted metabolomics can discriminate between sauces of different origins. Fermented and non-fermented soy sauces contain different volatile profiles. The aroma characteristics of soy sauce differ according to production methods. Abstract: Fermented soy sauce is used worldwide to enhance the flavour of many dishes. Many types of soy sauce are on the market, and their differences are mostly related to the country of origin, the production process applied and the ratio of ingredients used. Consequently, several aromas, tastes, colours, and textures are obtained. Nowadays, soy sauce can also be produced without microorganisms making the process shorter and cheaper. However, flavour may be lost. We have carried out a comprehensive metabolomics analysis of volatile compounds using stir bar sorptive extraction (SBSE)-GC–MS to relate differences in volatile content to production history and origin. The results revealed major differences between fermented and non-fermented soy sauces, and a list of volatile compounds is reported as being characteristic of each type. This study was able to relate volatiles to the production process using SBSE-GC–MS and to aroma characteristics using GC-O-MS.